2008
DOI: 10.1108/02640470810864136
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the second survey on electronic databases usage at Ankara University Digital Library

Abstract: Purpose -The purpose of this paper is to encompass the assessment of the effectiveness of the digital library and the value of multidisciplinary databases in terms of user preferences and use frequency by academic ranking. Another result of the survey is that many of the faculty members, although not all, use electronic databases. The most preferred databases have been Web of Science, Science Direct and Ebsco. When use of the electronic databases is analyzed, in respect of faculty rank and level of awareness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…He concluded that humanities students found the e-resources less important than the students of other disciplines. Talja and Maula (2003) and Atakan et al (2008) made the similar assertions that disciplinary differences can actually influence the usage of databases. Hong Sinh and Thi Hong Nhung (2012) argued that users' behavior like, purpose of usage, preferred types of materials, search techniques, ways to learn the search, and expectations and difficulties in using the e-resource can also influence the usage.…”
Section: Literature Reviewmentioning
confidence: 69%
See 1 more Smart Citation
“…He concluded that humanities students found the e-resources less important than the students of other disciplines. Talja and Maula (2003) and Atakan et al (2008) made the similar assertions that disciplinary differences can actually influence the usage of databases. Hong Sinh and Thi Hong Nhung (2012) argued that users' behavior like, purpose of usage, preferred types of materials, search techniques, ways to learn the search, and expectations and difficulties in using the e-resource can also influence the usage.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Users are either aware of the resources and use them, or aware, but do not use them, or sometimes they are unaware and therefore do not use them. Studies, such as Atakan et al (2008), Chirra and Madhusudhan (2009), Dee and Stanley (2005), Eskola (2005), Haines (2010) all found that users were aware of the digital information resources and used them. For example, Haines (2010) in a survey on the use of electronic resources by undergraduate and post-graduate students of basic sciences at the University of Vermont, United States, revealed that all the respondents (100%) were aware of the digital information resources of the university and accessed them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2002 and 2005, a survey was conducted at Ankara University to examine the usage of electronic databases. 7 A high rate of usage was identified among academic personnel who relied heavily on e-databases to discover scholarly literature. The survey also discovered the great difficulties that scholars encounter when selecting appropriate databases, particularly for those who were new to the library resources.…”
Section: Problems and Solutionsmentioning
confidence: 99%
“…1 At the same time, a wealth of fantastic free online resources available to libraries can also help enrich their electronic collection. It is crucial that both types of resources be readily accessible for library users through the library's web site.…”
Section: Introductionmentioning
confidence: 99%
“…For example, students faced difficulties in interacting with, operating, and using databases. Moreover, the user interface of these databases makes users’ access to information more difficult and causes confusion (6–8). One of the ways that can help to fix this problem is the application of valid models and theories that are available to study students’ acceptance patterns and their application of these databases.…”
Section: Introductionmentioning
confidence: 99%